Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

For $a_1,...,a_n,b_1,...,b_n>0,\quad$ define $a:=\sum a_i,\ b:=\sum b_i,\ s:=\sum \sqrt{a_ib_i}$.

Is the following inequality true?: $${\frac{\Bigl(\prod a_i^{a_i}\Bigr)^\frac1a}a \cdot \frac{\left(\prod b_i^{b_i}\right)^\frac1b}b \le\left(\frac{\prod (a_ib_i)^{ \sqrt{a_ib_i}}}{s^{2s}}\right)^\frac s{ab}}.$$ If true, how can I prove it? And if not true, is there a counter-example?


An alternate formulation of this inequality, as suggested by cardinal is

$$\sum_i x_i^2 \log x_i^2 + \sum_i y_i^2 \log y_i^2 \leq \rho^2 \sum_i \frac{x_iy_i}{\rho} \log \frac{x_iy_i}{\rho} \; ,$$

in which $x_i,y_i>0$, $\sum_i x_i^2 = \sum_i y_i^2 = 1$ and $\sum_i x_i y_i = \rho$. It can be found by taking the logarithm of the original expression and defining $x_i=\sqrt{a_i/a}$ and $y_i=\sqrt{b_i/b}$.

share|improve this question
    
My answer is wrong. I should have done the limit by hand... –  Beni Bogosel May 26 '11 at 22:00
13  
Let $u_i = a_i / a$, $v_i = b_i / b$ and $w_i = \sqrt{a_i b_i} / s$. Then, the inequality in the question is equivalent to the inequality $\sum u_i \log u_i + \sum v_i \log v_i \leq \frac{2 s^2}{a b} \sum w_i \log w_i$. Note that $(u_i)$, $(v_i)$ and $(w_i)$ are all in the $(n-1)$-simplex and so correspond to discrete probability measures on $\{1,\ldots,n\}$. Probabilistically, we might rewrite this as $H(u) + H(v) \geq \frac{2 s^2}{a b} H(w)$ where $H(\cdot)$ denotes the Shannon entropy. –  cardinal May 27 '11 at 13:11
4  
Note also that there is a, perhaps, interesting element of symmetry at play here. In both the OP's question and my previous remark, the left-hand side is permutation invariant with respect to the relative ordering of the coordinates of $(a_i)$ and $(b_i)$, whereas the right-hand side is not. In particular, let $s_\pi = \sum \sqrt{a_i b_{\pi(i)}}$, $w_{i,\pi} = \sqrt{a_i b_{\pi(i)})}/s_\pi$, and $w_\pi = (w_{i,\pi})$. Then $H(u) + H(v) \geq \frac{2}{n! ab} \sum_{\pi \in S_n} s_\pi^2 H(w_\pi)$ and $H(u) + H(v) \geq \frac{2}{ab} \max_{\pi \in S_n} s_\pi^2 H(w_\pi)$. –  cardinal May 28 '11 at 6:31
    
Yes, exactly... May we prove it for some small values of $n$? e.g. $n=3$ or $n=4$. –  Amir Hossein May 30 '11 at 5:26
2  
@Amir Where did this problem come from? –  JavaMan May 30 '11 at 21:11
show 8 more comments

2 Answers 2

up vote 9 down vote accepted
+100

This is slightly too long to be comment, though this is not an answer:


Edit: I am providing a few revisions, but I still have not found a proof.

My previous comment was not quite correct. I "rearranged" the inequality by raising both sides of the inequality to certain powers, and I did not take into account that we do not know a priori whether any of the terms are larger or smaller than $1$. Depending on the size of each term (in particular, whether it is smaller or larger than $1$), exponentiating both sides could potentially reverse the inequality. I have returned the question to its original form as suggested by the OP, and I have added one more observation.


Let me first say that I have been working on this question for a bit, and though I have not yet resolved it, I have been having fun trying!

Now, to emphasize the dependence on $n$, let's set

$$ \alpha_n = \sum_{i=1}^n a_i \qquad \beta_n = \sum_{i=1}^n b_i, \qquad \sigma_n = \sum_{i=1}^n c_i, $$

where $c_i = \sqrt{a_i b_i}$. Further, let's put

$$ A_n = \prod_{i=1}^n (a_i)^{a_i}, \qquad B_n = \prod_{i=1}^n (b_i)^{b_i}, \qquad S_n = \prod_{i=1}^n (c_i)^{c_i}. $$

Our goal is to show:

\begin{equation} (1) \hspace{1in} \left(\frac{A_n}{(\alpha_n)^{\alpha_n}}\right)^{\frac{1}{\alpha_n}} \cdot \left(\frac{B_n}{(\beta_n)^{\beta_n}} \right)^{\frac{1}{\beta_n}} \leq \left(\frac{S_n}{(\sigma_n)^{\sigma_n}}\right)^{\frac{2\sigma_n}{\alpha_n \beta_n}} \end{equation}

A few pedestrian observations:

  • If $a_i = b_i$ for $i = 1, \dots , n$ (which forces $c_i = a_i = b_i$), then $A_n = B_n = S_n$, we also have $\alpha_n = \beta_n = \sigma_n$, and (1) holds in this case.

  • Note that $2c_i \leq a_i + b_i$ as $2xy \leq x^2 + y^2$ for all real numbers $x, y$. Hence, $2\sigma_n \leq \alpha_n + \beta_n$. Furthermore, Cauchy-Schwarz gives $\sigma_n^2 \leq \alpha_n \beta_n$. Both of these observations imply that $(\sigma_n + 1)^2 \leq (\alpha_n + 1)(\beta_n + 1)$.

I would imagine that with enough creativity, one may find a proof of the inequality involving convexity or a simple application of the AM-GM inequality (which I suppose is much the same thing!).

I have been unable to prove the inequality even in the case $n = 2$, when I assume $\alpha_n = \beta_n = 1$. I am not hopeful for a proof of the general case.

share|improve this answer
1  
Thanks for the start! I'm still waiting for a solution to this problem... –  Amir Hossein May 28 '11 at 5:13
1  
@Amir: And I'm still thinking about it (: –  JavaMan May 28 '11 at 15:10
    
BUMP this! Anyone? Just three days remaining... –  Amir Hossein Jun 2 '11 at 8:54
    
The bounty was going to be expired, so I gave it to DJC's post. Problem hasn't been solved yet, if anyone got anything, please share it with us. –  Amir Hossein Jun 4 '11 at 2:46
    
@Amir: I did not contribute to a solution of the problem at hand despite my efforts, and while I'm flattered to get the points, I simply don't deserve them. If there is a way to undo the points, I'm fine if they get taken away. –  JavaMan Jun 4 '11 at 3:24
show 2 more comments

The inequality is true.

I posted cardinal's reformulation on Math Overflow, as I was very interested in seeing the problem resolved. A complete solution was provided by fedja, and it can be found here. Using the inequality $$ \sqrt{\frac{a_i b_i}{ab}}\leq \sum_{i=1}^n\sqrt{\frac{a_i b_i}{ab}}\leq \sqrt{\frac{a_i b_i}{ab}}+\sqrt{\frac{(a-a_i)(b- b_i)}{ab}},$$ which follows from Cauchy-Schwarz, fedja was able to consider the inequality entry-wise. Doing so, the problem was reduced to showing

(key inequality) For $x,y,z>0$ and $xy=z^2$, we have $$(1+x)\log(1+y)+(1+y)\log(1+x)\geq 2(1+z)\log(1+z).$$

Fedja gave a proof of this inequality in his answer, and the user Babylon5 gave an alternate proof on AoPS.

share|improve this answer
add comment

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.